A Compact "Water Window" Microscope with 60 nm Spatial Resolution for Applications in Biology and Nanotechnology - Wachulak, Przemyslaw; Torrisi, Alfio; Nawaz, Muhammad F; Bartnik, Andrzej; Adjei, Daniel; Vondrová, Šárka; Turňová, Jana; Jančarek, Alexandr; Limpouch, Jiří; Vrbová, Miroslava; Fiedorowicz, Henryk (Microscopy and microanalysis, 2015)
Short illumination wavelength allows an extension of the diffraction limit toward nanometer scale; thus, improving spatial resolution in optical systems. Soft X-ray (SXR) radiation, from "water window" spectral range, λ=2.3-4.4 nm wavelength, which is particularly suitable for biological imaging due to natural optical contrast provides better spatial resolution than one obtained with visible light microscopes. The high contrast in the "water window" is obtained because of selective radiation absorption by carbon and water, which are constituents of the biological samples. The development of SXR microscopes permits the visualization of features on the nanometer scale, but often with a tradeoff, which can be seen between the exposure time and the size and complexity of the microscopes. Thus, herein, we present a desk-top system, which overcomes the already mentioned limitations and is capable of resolving 60 nm features with very short exposure time. Even though the system is in its initial stage of development, we present different applications of the system for biology and nanotechnology. Construction of the microscope with recently acquired images of various samples will be presented and discussed. Such a high resolution imaging system represents an interesting solution for biomedical, material science, and nanotechnology applications.
Keywords: Image Processing, Computer-Assisted; voda; mikroskopie; Mice; zvířata; Soft X-rays (SXR); gas puff target source; Colonic Neoplasms; uhlík; nanotechnologie; “water window”; Nanotechnology; rentgenové záření; karcinom; počítačové zpracování obrazu; myši; nádory tračníku; Animals; SXR microscopy; X-Rays; Biology; Microscopy; Carbon; Fresnel zone plates; fibroblasty; Carcinoma; Fibroblasts; biologie; Water